A new introduction to Islam rulers, rebels, and rogues - Brown, Daniel W. (John Wiley & Sons, Ltd., 2017)
Covering the origins, key features, and legacy of the Islamic tradition, the third edition of A New Introduction to Islam includes new material on Islam in the 21st century and discussions of the impact of historical ideas, literature, and movements on contemporary trends. Features study questions for each chapter and more illustrative material, charts, and excerpts from primary sources.